The right of access to agricultural land? Comments on human rights and land grabbing - Pastuszko, Radosław (Przegląd Prawa Rolnego, 2025)
This article aims to establish a theoretical framework for the concept of the right of access to agricultural land (agricultural land resources) as a mechanism for safeguarding human rights in the context of land acquisitions. According to contemporary soft law instruments, the right of access to agricultural land may be recognised as an autonomous concept. This concept is characterised by a specific dualism, encompassing both the individual and collective dimensions. The article analyses the mechanisms of human rights violations resulting from large-scale land acquisitions, paying particular attention to the right to food, property rights, and the collective rights of indigenous peoples and local communities. The right of access to agricultural land is a broader concept than the classic right of ownership. It encompasses various forms of land tenure, including customary and informal ones, and requires the application of different protection mechanisms for the individual and collective dimensions.